An Undefined Something Else: Barthes, Culture, Neutral Life. (July 2020) - Badmington, Neil
How might Roland Barthes' posthumously published account of the Neutral invite us to rethink the very activity of cultural analysis? How did Barthes the cultural critic change when, towards the end of his career, he described and desired Neutral Life? Cultural criticism has often taken Barthes' early semiological work as a guide, but this essay examines how we might need to reorient ourselves as critics, shift our stance, learn to look and live differently in the light of Barthes' later focus on the Neutral.